Insulin resistance in gestational diabetes in female dogs (Clinical case) - Боброва, В. В. (Scientific Progress & Innovations, 2018)
Diabetes mellitus is a fairly common disease among humans and animals. Today veterinarians mark a certain increase in the number of dogs and cats diagnosed with diabetes mellitus. It is a hormonal disease characterized by the presence of hyperglycemia and permanent glucosuria. The causes of diabetes are absolute or relative insufficiency of insulin synthesis by the pancreas (first type or insulin dependent diabetes, more common in dogs) and insulin resistance of the body with β-cell dysfunction (second type or non-insulin dependent diabetes, more commonly sick of cats). Permanent degeneration of β-cells occurs due to enhanced insulin synthesis. Treatment in the first and second cases is carried out by insulin. In animals with diabetes, polydipsia/polyuria syndrome is manifest, may be complications in the form of ketoacidosis, which is characterized by significant violations of acid-alkaline and electrolyte balances, which directly endangers life. Separate secretion of secondary or transient diabetes, which occurs due to the development of another disease – pancreatitis, hyperadrenocorticism or long-term use of progestogens and glucocorticoids. Timely detection and treatment of the primary disease with the neutralization of the causes of hyperglycemia to the desolation of β-cells can lead to recovery. It also applies to gestational diabetes mellitus, which may occur during the late pregnancy or diestrus in a female dog, when high levels of progesterone, somatotropin and structurally similar hormones cause the appearance of insulin resistance of the tissues of the body. Timely control of hyperglycemia and subsequent ovariogestarterectomy contributes to the recovery of the animal. Unfortunately, the issue of controlling hyperglycemia in the occurrence of insulin resistance in the treatment of diabetes is very complicated and does not provide immediate results. The paper presents an analysis of the clinical case of insulin resistance in gestational diabetes in a non-sterilized female dog.